KANDUNGAN GIZI DAN ORGANOLEPTIK BISKUIT SUBSTITUSI TEPUNG IKAN GABUS DAN TEPUNG DAUN KATUK SEBAGAI ALTERNATIF CAMILAN IBU MENYUSUI - Nupitasari, Putri; Muhlishoh, Arwin; Ma’rifah, Bahriyatul (Jurnal Gizi dan Pangan Soedirman, 2023)
This study aims to determine the effect of substitution of snakehead fish flour and katuk leaf flour on the macronutrient content, iron and organoleptic properties of biscuits. This study used a completely randomized design (CRD) with ratio of snakehead fish flour and katuk leaf flour, namely: F1 (35%:10%), F2(40%:15%), F3 (45%:20%). Organoleptic tests included color, taste, texture, aroma and after taste by observation with 30 panelists. Nutrient content and Fe were analyzed using one way ANOVA and Duncan's further test. While the organoleptic was analyzed using Kruskal Wallis and Mann Whitney advanced test. Based on the test results for the nutritional content of biscuits, it was found that each successive formulation contained 8.63%, 7.12%, 7.77% moisture content, 2.31%, 2.64%, 2.89% ash content, 21.86% protein, 24.20%, 25.10%, 17.59% fat, 17.66%, 17.74%, carbohydrates 49.55%, 43.29%, 46.63%, iron 7.47%, 9.01%, 9.35%. Based on the organoleptic test of taste and after taste the most preferred is F2, the preferred color and taste is F3, while the texture is F1. The selected biscuit formulation is a substitute for snakehead fish and katuk leaf flour, namely F3. F3 meets the 11.5% AKG for protein and iron and can be claimed as a food source of protein and iron for lactating mothers 19-29 years (first trimester).